The sociology of entrepreneurship - Ruef, Martin; Lounsbury, Michael (Research in the sociology of organizations, 2007)
This volume takes stock of entrepreneurship research within organizational sociology, critically examining the theoretical presuppositions of the field and situating extant research within the sociological canon. The contributors to this volume exemplify how the disciplinary lens of sociology provides a systematic foundation to understand the context, process, and effects of entrepreneurial activity. Topics explored include entry into entrepreneurship, immigrant entrepreneurship and enclaves, academic entrepreneurship, and entrepreneurialism related to new organizational forms.The breadth and depth of the research offered by the esteemed scholars that have contributed to this volume highlight the progressive nature of sociological research on entrepreneurship. Taken as a whole, the volume points the way towards a more comprehensive framework for the development of the sociology of entrepreneurship. Research in the Sociology of Organizations is an international series. It is especially concerned with specifying the unique contributions of sociological theories and research techniques to the analysis of organizations. Each volume aims to foster debate and dialogue about the value of new theories and research to the field of organizational sociology as well as the growing international community of organizational scholars.